1965
DOI: 10.1121/1.1939407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noise at One Ear on the Detection of Signals at the Other Ear

Abstract: Detection of a tonal signal in noise at one ear improves in proportion to the level of correlated noise in the “off” ear up to the point of equal noise levels in the two ears. A given level of correlated noise at the “off” ear produces a nearly constant improvement in detection over monaural masking independent of the signal-to-noise ratio in the ear receiving the signal. A given level of uncorrelated noise at the “off” ear, however, has the opposite effect. It produces a nearly constant decrease in detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The purpose of the experiment reported here was to determine the intensity at which this occurred, and to establish the form of the function relating the magnitude of the MLD to the noise level in the ear with the less intense noise. Blodgett, Jeffress, and Whitworth (1962), Mulligan and Wilbanks (1965), Weston and Miller (1965), Egan (1965), Dolan (1966), and Dolan and Robinson (1967) have published data relevant to this weakness of the Jeffress model. All of these investigators used conditions of binaural noise and monaural signal (e.g., N0-Sm, N•r-Sm) and varied the spectrum level of the nonsignal ear.…”
Section: Figure L(a) Is a Vector Construction Representing An Instantmentioning
confidence: 99%
“…The purpose of the experiment reported here was to determine the intensity at which this occurred, and to establish the form of the function relating the magnitude of the MLD to the noise level in the ear with the less intense noise. Blodgett, Jeffress, and Whitworth (1962), Mulligan and Wilbanks (1965), Weston and Miller (1965), Egan (1965), Dolan (1966), and Dolan and Robinson (1967) have published data relevant to this weakness of the Jeffress model. All of these investigators used conditions of binaural noise and monaural signal (e.g., N0-Sm, N•r-Sm) and varied the spectrum level of the nonsignal ear.…”
Section: Figure L(a) Is a Vector Construction Representing An Instantmentioning
confidence: 99%
“…Eight years later, it was found that the tonal signal and noise presented to one ear led to the same masking threshold as these presented to both ears [3]. In 1965, Mulligan and Wilbanks reported that a certain level of correlated noise in the ear without signal improved the detection of a tonal signal in noise, while the uncorrelated noise had the opposite effect [4]. It was confirmed that a given level of the correlated noise in the contralateral ear produced a constant increment in detection independent of the SNR in the signal ear [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 1965, Mulligan and Wilbanks reported that a certain level of correlated noise in the ear without signal improved the detection of a tonal signal in noise, while the uncorrelated noise had the opposite effect [4]. It was confirmed that a given level of the correlated noise in the contralateral ear produced a constant increment in detection independent of the SNR in the signal ear [4]. It was also found that the additional noise to the empty ear could reduce the threshold for the tonal signal presented only to one ear mixed with noise [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Under optimal conditions, when a signal and a noise are presented to both ears and one or the other is reversed in phase, the signal can be detected at a level on the order of 18 dB lower than when both are in phase (Blodgett, Jeffress, &Taylor, 1958 ;Jeffress, Blodgett, &Deatherage, 1952Jeffress, et al, 1956 ;Webster, 1951) . Also, the detection of a tonal signal at one ear, partially masked by a noise at that ear, can be improved by as much as 10 dB when identical noise is added at the other ear (Blodgett, Jeffress , & Whitworth, 1962;Mulligan & Wilbanks, 1965 ;Weston & Miller, 1965;Wilbanks & Whitmore, 1968). In both cases, the signal to which the observer responds is too weak to be detected by mono aural means.…”
mentioning
confidence: 99%